Cytotoxicity Study of Plantago major L. Extracts on RAW 264.7 Macrophages - Ahmad Marzuki; Triana Hertiani; Retno Murwanti; Kurnia Rahayu Purnomo Sari; Almira Rahmayani (Majalah Obat Tradisional, 2025)
The use of medicinal plants in modern medicine is on the rise, particularly in addressing diabetes and its associated complications, such as persistent inflammatory wounds. Plantago major L. (P. major) is known for its rich distribution of bioactive compounds and its efficacy in treating diabetes, wound healing, inflammation, and oxidative stress. Before in vitro drug efficacy testing, it is essential to assess the toxicity of P. major extract. This study aims to evaluate the toxicity of P. major extracts on RAW 264.7 cells cultured in high-glucose DMEM media. This preliminary assessment is crucial for determining safe extract concentrations for subsequent anti-inflammatory activity testing using macrophage cells cultured in a hyperglycemic condition. Extracts were obtained from both leaf and non-leaf parts using maceration and UAE methods, resulting in four extract types: macerated leaf (DM), UAE leaf (DU), macerated non-leaf (NM), and UAE non-leaf (NU). Each extract was prepared in seven concentration series ranging from 7.81 to 500 μg/mL. Toxicity was assessed using the MTT method to determine cell viability after a 4-hour incubation. Significance against the control was analyzed using one-way ANOVA, and the effects of different plant parts, extraction methods, and their interaction were evaluated using two-way ANOVA. Results indicated that concentrations of 7.81-500 μg/mL for all four extracts did not significantly reduce cell viability (p > 0.05) compared to the control, with leaf extracts exhibiting higher viability percentages than non-leaf extracts, especially with the UAE extraction method at a concentration of 250 μg/mL (106.73 ± 4.20%). Variations in plant parts significantly affected (p < 0.05) cell viability percentages, whereas differences in extraction methods and their interaction did not have a significant effect. In conclusion, this study demonstrates that the four extracts at concentrations of 7.81-500 μg/mL are non-toxic to RAW 264.7 cells. Therefore, they are safe to use in anti-inflammatory activity testing.